How to protect the patent right in a standardization context—property rule or liability rule? - Tyanyi Ren (Market and Competition Law Review)
High transaction costs are involved in the SEPs licensing process, and the FRAND policy essentially represents a collaborative effort by SSO members to reduce such costs. In order to facilitate the SEPs licensing process, the law must operate in a way that promotes the effective implementation of the FRAND cooperation mechanism. To achieve this goal, appropriate remedies for SEPs matter significantly. According to the transaction cost theory, SEPs should be protected by the property rule rather than the liability rule, and the parties’ subjective fault demonstrated during the negotiation process is not the deciding factor for the issuance of an injunction, but merely a factor to be considered when determining the amount of damages. The eBay ruling provided factors to identify the appropriate remedies to reduce transaction costs for patent licensing, which do not consider the subjective fault of both parties. The problem with the application of the eBay rule in FRAND-related cases currently by U.S. courts is that it links subjective fault to the issuance of an injunction inappropriately. The EU addressed the issue under the competition law perspective; however, it improperly expanded the scope of antitrust law regulating FRAND-related issues, rigidly linking the issuance of an injunction to the party’s subjective fault. The court’s definition of subjective fault is constantly changing, which means that the number of FRAND-related disputes will continue to increase. The scope of antitrust law applicable to FRAND disputes should be limited; in this case, the German courts established an appropriate standard in the Orange Book Standards.